MODEL EKOSISTEM INOVASI UNIVERSITAS (STUDI KASUS DI BANDUNG TECHNO PARK) - Sahara Syarifatul Choeriyah; Siska Noviaristanti (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The establishment of a national innovation system is necessary to encourage innovation and socio-economic development. The most important thing in the innovation system is the collaboration of academic, business, community, and government in the innovation ecosystem. The purpose of this study is to determine the actors involved from each entity in the innovation ecosystem, the relationship between actors, and the impact of the relationship between actors. Through case study research method with the object of research at Bandung Techno Park at Telkom University, this study investigates the mutual relationship between entities. Value network analysis is then used to model the innovation ecosystem. This study uses a qualitative method with data collection through interviews with 14 speakers representing each entity. The research results obtained that not all entities have actors who involved in the innovation ecosystem. Some obstacles such as the quality of research, lack of researchers’ ability to see market conditions so that innovative products are considered not following the needs of consumers and industries in Indonesia that dominated by agricultural-based industries becomes a difficulty in commercializing technological innovation through licensing. This research shows that BTP’s role as Technology Transfer Officer still has shortcomings to align the results of research from academic with business needs. In addition, government regulation has not fully sided with domestic technological innovations to develop. Keywords: university, innovation ecosystem, value network analysis, qualitative method, techno park.